Pengembangan Media “Kanca” (Keseimbangan Angka Ceria) Berbasis Local Culture - Purwinda, Afri; Sari, Tita Tanjung; Kadarisman, Kadarisman (Scholarly Journal of Elementary School, 2023)
Creative learning media is very influential on the process and student learning outcomes, one of which is "Kanca" media. "Kanca" media is arithmetic media that can be used in grade 1 students. This study aims to: (1) describe the development of local culture-based "kanca" media (2) find out the response of teachers and students to the development of local culture-based "kanca" media.This study uses the ADDIE research method developed by Dick and Carry which consists of 5 stages, namely analysis, design, development, implementation, evaluation. Kanca was tested in limited trials and field trials in grade I public elementary schools Pojah II and Paberasan I. Product eligibility was based on media experts, material, teacher responses, student responses. The results showed: (1) "kanca" media was developed using the ADDIE development model, the media expert's assessment obtained a 98%, the material expert's assessment obtained a 97.5% of the criteria "Highly Appropriate and Not Revised", (2) the assessment of student responses in the limited trial obtained a 92.5%, the of teacher responses and students in the field trial obtained a 100% and 93,6% of the "Very Good" criteria, local culture-based "Kanca" media can be used as an alternative media for learning mathematics.